The Fluorescent Two-Hybrid Assay to Screen for Protein–Protein Interaction Inhibitors in Live Cells: Targeting the Interaction of p53 with Mdm2 and Mdm4. (April 2014) - Yurlova, Larisa; Derks, Maarten; Buchfellner, Andrea; Hickson, Ian; Janssen, Marc; Morrison, Denise; Stansfield, Ian; Brown, Christopher J.; Ghadessy, Farid J.; Lane, David P.; Rothbauer, Ulrich; Zolghadr, Kourosh; et al.
Protein–protein interactions (PPIs) are attractive but challenging targets for drug discovery. To overcome numerous limitations of the currently available cell-based PPI assays, we have recently established a fully reversible microscopy-assisted fluorescent two-hybrid (F2H) assay. The F2H assay offers a fast and straightforward readout: an interaction-dependent co-localization of two distinguishable fluorescent signals at a defined spot in the nucleus of mammalian cells. We developed two reversible F2H assays for the interactions between the tumor suppressor p53 and its negative regulators, Mdm2 and Mdm4. We then performed a pilot F2H screen with a subset of compounds, including small molecules (such as Nutlin-3) and stapled peptides. We identified five cell-penetrating compounds as potent p53–Mdm2 inhibitors. However, none exhibited intracellular activity on p53–Mdm4. Live cell data generated by the F2H assays enable the characterization of stapled peptides based on their ability to penetrate cells and disrupt p53–Mdm2 interaction as well as p53–Mdm4 interaction. Here, we show that the F2H assays enable side-by-side analysis of substances' dual Mdm2–Mdm4 activity. In addition, they are suitable for testing various types of compounds (e.g., small molecules and peptidic inhibitors) and concurrently provide initial data on cellular toxicity. Furthermore, F2H assays readily allow real-time visualization of PPI dynamics in living cells.